Rejuvenation of Facial Skin Using Fractional Er: YAG Laser - kadhem, Ali A.; Al Saad, Athir M.; Toama, Ali S. (Iraqi Journal of Laser, 2020)
Fractional Er: YAG laser resurfacing is increasingly used for treating rhytides and photo aged skin because of its favorable benefit‐risk ratio. The multi-stacking and variable pulse width technology opened a wide horizon of rejuvenation treatments using this type of laser. To evaluate the efficacy and safety of the use of fractional 2940 nm Er: YAG laser in facial skin rejuvenation. Twelve female patients with mean age 48.3 years and multiple degrees of aging signs and solar skin damages, were treated with 2 sessions, one month apart by fractional Er: YAG laser. Each session consisted of 2 steps, the first step employed the use of the multi stack ablative fractional mode and the fractional long pulsed non-ablative mode settings were used in the second step. The results were assessed 4-8weeks after the last session by using the wrinkles assessment scale improvement, the improvement in the degree of dyschromia and keratosis, the degree of patients' satisfaction and rate of complications. The mean improvement in Wrinkles assessment scale was very satisfying. The improvement in keratosis was good to excellent in 66.7% of patients compared to 33.3% of patients who were mildly to moderately improved. Dyschromia improvement, 50% of the patients had good to excellent results versus 50% who had mild to moderate improvement. 75% of patients were well satisfied, 16.6% were moderately satisfied and 8.3% were unsatisfied. Total incidence of complications was 16.6%, where 1 patient had herpes infection and a second patient had milia. The use of Er: YAG laser in fractional ablative and fractional long pulse non ablative modes for facial rejuvenation is an effective, safe, with short down time and low complication rate.